2021
DOI: 10.1177/1550059421991688
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Recognition Deficits in Psychiatric Disorders as a Target of Non-invasive Neuromodulation: A Systematic Review

Abstract: Background. Social cognition deficits are a core feature of psychiatric disorders, such as schizophrenia and mood disorder, and deteriorate the functionality of patients. However, no definite strategy has been established to treat social cognition (eg, emotion recognition) impairments in these illnesses. Here, we provide a systematic review of the literature regarding transcranial direct current stimulation (tDCS) and repetitive transcranial magnetic stimulation (rTMS) for the treatment of social cognition def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 63 publications
0
28
0
Order By: Relevance
“…The effect sizes of tDCS for this benefit were about 0.5 SD) (Table 5), which is considered clinically meaningful (7). By contrast, its immediate effects after 1-2 sessions tDCS have been reported not to improve social cognitive disturbances (Table 1) (13,(17)(18)(19). As social cognition is considered to be directly linked to realworld social functioning (3,10), multisession tDCS, rather than single-session tDCS, may provide benefits for functional recovery in patients with schizophrenia.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The effect sizes of tDCS for this benefit were about 0.5 SD) (Table 5), which is considered clinically meaningful (7). By contrast, its immediate effects after 1-2 sessions tDCS have been reported not to improve social cognitive disturbances (Table 1) (13,(17)(18)(19). As social cognition is considered to be directly linked to realworld social functioning (3,10), multisession tDCS, rather than single-session tDCS, may provide benefits for functional recovery in patients with schizophrenia.…”
Section: Discussionmentioning
confidence: 97%
“…So far, three studies have been conducted to examine the ability of tDCS to improve social cognitive disturbances of schizophrenia (see Table 1) (13,(17)(18)(19). Among them, only one study reported facilitative effects of stimulation on the left prefrontal cortex on emotion recognition (19).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…the arcuate fasciculus (AF)) may support both language and ToM networks. Finally, we note that recent lesion analysis studies and cognitive stimulation mapping results also point to more broadly distributed cortical regions and additional white matter tracts involved in supporting these functions ( Drane and Pedersen, 2019 ; Yamada et al, 2021 ) than reflected by the classical models (i.e., language models that connect Wernicke’s to Broca’s area via the AF Geschwind, 1970 and ToM models that include the right temporal parietal junction as a critical hub Saxe and Wexler, 2005 ).…”
Section: Introductionmentioning
confidence: 76%